Study on Starch-Based Thickeners in Chyme for Dysphagia Use - Youdong Li; Lingying Li; Guoyan Liu; Li Liang; Xiaofang Liu; Jixian Zhang; Chaoting Wen; Xin Xu (Foods)
A dysphagia diet is a special dietary programme. The development and design of foods for dysphagia should consider both swallowing safety and food nutritional quality. In this study, we investigated the rheological properties (viscosity, thixotropy, and viscoelasticity), textural properties, and swallowing behaviour of commercially available natural, pregelatinised, acetylated, and phosphorylated maize starch and tapioca starch. The results showed that all the samples belonged to food grade 3 in the framework of the International Dysphagia Dietary Standardization Initiative (IDDSI) and exhibited shear-thinning behaviour in favour of dysphagia patients, except for the sample containing pregelatinised starch, which was grade 2. Rheological tests showed that the samples had good structural recovery properties. At the same starch concentration, the elastic modulus of phosphorylated cassava starch FSMP was significantly greater than that of the starch solution, whereas that of acetylated starch was significantly less than that of the starch solution, and the combination of acetylated starch and protein led to a significant viscosity reduction phenomenon, resulting in FSMPs with good stability and fluidity; this may provide an opportunity for the incorporation of more high-energy substructures. The textural results showed that all the samples possessed textural properties of low hardness, low adhesion, and high cohesion, all of which could be used as food for dysphagia patients. This study may provide a theoretical basis for the creation and design of novel nutritional foods for dysphagia.